LEVELS OF PHYSICAL ACTIVITY AMONG MEDICAL STUDENTS IN KALABURAGI, NORTH KARNATAKA: A CROSS-SECTIONAL SURVEY - VADIVEL, KAMALAKANNAN; PRASHANTH TALIKOTI,; SHILPA MANOHAR KAMBLE,; NILESH N KATE, (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: Physical activity (PA) is associated with several health benefits. Level of PA among undergraduate medical students is less studied. The objective of the study is to assess the level of PA among medical students in a medical college in North Karnataka, Kalburgi district. Methods: A cross-sectional survey using Global Physical Activity Questionnaire version 2 developed by the WHO was done among 167 study participants. The ration of male to female were 69:98. The total level of PA in three domains, namely, work-related PA, travel to and from places-related PA and leisure time PA were calculated and were expressed as MET-min per week. Results: About 90% of the students have PA levels over 600 MET-min per week. 10% of students showed inactive PA levels (<600 MET-min per week). The level of PA during work was more than the travel to and from places-related PA and leisure time PA. Male participants were found to be significantly more active than female participants in work-related PA and leisure time vigorous PA. Travel-related PA was similar in both male and female participants. Conclusion: The study provides MET-min per week score in undergraduate medical student which could provide baseline values for students of a medical college in North Karnataka. The data collected could be compared with the values obtained from other part of the state and our country.